The king's stilts - Seuss, Dr. (New York : Random House, 1967)
The king wears his stilts every day after work--until they are stolen by a wicked man. Then the Nizzards invade the country until Eric, the king's page boy, finally recovers the stilts and the country is saved.
Library Journal
4.6
K-3
Keywords: Stilts -- Fiction; Kings, queens, rulers, etc. -- Fiction; Fantasy; Stilts -- Fiction; Kings and rulers -- Fiction; Fantasy fiction